Optic disc vessel density in nonglaucomatous and glaucomatous eyes: an enhanced-depth imaging optical coherence tomography angiography study - Yoshikawa Y (Dove Medical Press, 2018)
Yuji Yoshikawa,1 Takuhei Shoji,1 Junji Kanno,1 Itaru Kimura,1 Masanori Hangai,2 Kei Shinoda1 1Department of Ophthalmology, Saitama Medical University, Saitama, Japan; 2Hangai Eye Institute, Saitama, Japan Purpose: To evaluate the ability of enhanced-depth imaging (EDI) optical coherence tomography angiography (OCTA) to detect vascular signals inside the glaucomatous optic disc.Patients and methods: Ten glaucomatous eyes of 8 subjects and 11 nonglaucomatous eyes of 7 subjects underwent EDI and conventional OCTA for optic disc analysis. The optic disc vessel density (VD) at maximum scan depth (2 mm) was compared between the 2 methods and between glaucomatous and nonglaucomatous eyes. Regression analysis was used to determine the factors affecting disc VD.Results: The median (25th, 75th percentile) of the visual field mean deviation was –20.5 (–25.1, –13.5) dB in glaucoma. The disc VD measured with the EDI method was significantly greater than that measured with the conventional method in glaucoma and nonglaucoma. The disc VD was also significantly lower in glaucoma than in nonglaucoma. The disc VD and mean deviation were significantly and positively correlated in both methods (conventional: R2=0.27, EDI: R2=0.22).Conclusion: The correlation between disc VD and glaucoma severity was comparable between conventional and EDI measurements. Images obtained with EDI-OCTA have the additional benefit of revealing more vascular signals in deeper layers. The disc VD, as determined by both conventional and EDI-OCTA methods, may be an indicator of glaucoma severity. Keywords: optical coherence tomography angiography, enhanced-depth imaging, vessel density, glaucoma severity, mean deviation